2016
DOI: 10.1111/tbed.12481
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Viral Pathogens in African Simian Bushmeat Seized at A French Airport

Abstract: Illegal bushmeat traffic is an important threat to biodiversity conservation of several endangered species and may contribute to the emergence and spread of infectious diseases in humans. The hunting, manipulation and consumption of wildlife-based products, especially those of primate origin, may be a threat to human health; however, few studies have investigated the role of bushmeat trade and consumption as a potential source of human infections to date. In this study, we report the screening of viral pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Metagenomic studies have indicated the presence of a giant virus gene set in all continents (21)(22)(23)(24)(25). Some representatives, such as the mimivirus, appear to be more abundant and ubiquitous, containing hundreds of isolates already reported (21)(22)(23)(24)(25)(26). Pandoravirus-like sequences were also detected in metagenomic data from environmental samples (22,27,28) as well as from insects, simian bushmeat, and human plasma (23)(24)(25)27).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Metagenomic studies have indicated the presence of a giant virus gene set in all continents (21)(22)(23)(24)(25). Some representatives, such as the mimivirus, appear to be more abundant and ubiquitous, containing hundreds of isolates already reported (21)(22)(23)(24)(25)(26). Pandoravirus-like sequences were also detected in metagenomic data from environmental samples (22,27,28) as well as from insects, simian bushmeat, and human plasma (23)(24)(25)27).…”
Section: Discussionmentioning
confidence: 96%
“…Giant virus prospective studies have revealed an outstanding universe of viral diversity (3,4,6,(16)(17)(18)(19)(20). Metagenomic studies have indicated the presence of a giant virus gene set in all continents (21)(22)(23)(24)(25). Some representatives, such as the mimivirus, appear to be more abundant and ubiquitous, containing hundreds of isolates already reported (21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And human immunodeficiency viruses originated from primate bushmeat in West Africa (Ayouba et al, ; Gao et al, ; Hirsch, Olmsted, Murphey‐Corb, Purcell, & Johnson, ; Huet, Cheynier, Meyerhans, Roelants, & Wain‐Hobson, ; Keele et al, ; Plantier et al, ; Van Heuverswyn et al, ; Yamaguchi, Devare, & Brennan, ). In general, markets selling wildlife are particularly prone to facilitating the emergence of zoonotic pathogens (Greatorex et al, ), and this infected primate bushmeat is even being shipped worldwide (Smith et al, ; Temmam et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this approach has international implications, with risks of exotic zoonotic diseases associated with the huge quantities of illegal bush meat from central and west Africa being imported into Europe and North America. 12 Finally, naming of a new virus is important not only for virologists in the long term but also for effective communication to the general public. In all the major EZV events over the past 25 years, naming of the new virus has not been straightforward and most went through a renaming process (table).…”
Section: From Hendra To Wuhan: What Has Been Learned In Responding Tomentioning
confidence: 99%